(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This study revealed the importance of educational supervision, which is one of the most important elements of the educational process. The educational supervision accedes a leadership position in order to improve and develop all elements of the educational process through the development of the teachers’ educational competencies and help them highlight and develop educational curricula and educational materials. There is a need for educational supervision that focuses on all the elements of the educational situation and the internal and external conditions and factors related to this situation. The educational supervisor, according to his position, directs the elements of the educational process, including teachers, students and workers, towards carrying out a homogeneous integrative work that harnesses all the school capabilities of buildings, property, equipment and the like. The supervisor, the teacher, the student, the curriculum and school environment constitute sub-systems that interact with each other through an open system and in an atmosphere of cooperation, democracy and human relations that take into account the needs of the individual and the group in the educational field, which works to improve the performance of both the teacher and the educational supervisor and to obtain educational outcomes appropriate to the capabilities and resources available in the educational system.